Highly Stretchable Self‐Powered Wearable Electrical Energy Generator and Sensors. Issue 2 (6th December 2020) - Mokhtari, Fatemeh; Spinks, Geoffrey M.; Sayyar, Sepidar; Cheng, Zhenxiang; Ruhparwar, Arjang; Foroughi, Javad
Abstract: The ubiquity of wearables, coupled with the increasing demand for power, presents a unique opportunity for fiber‐based mobile energy generator systems. However, no commercially available systems currently exist with typical problems including low energy efficiency; short cycle life; slow and expensive manufacturing; and stiff, heavy or bulky componentry that reduce wearer comfort and aesthetic appeal. Herein, a new method is demonstrated to create wearable energy generators and sensors using nanostructured hybrid polyvinylidene fluoride (PVDF)/reduced graphene oxide (rGO)/barium‐titanium oxide (BT) piezoelectric fibers and exploiting the enormous variety of textile architectures. Highly stretchable piezoelectric fibers based on coiled PVDF/rGO/BT fibers energy generator and sensor are developed. It is found that the coiled PVDF/ rGO/BT enables to stretch up to ≈100% strain that produces a peak voltage output of ≈1.3 V with a peak power density of 3 W Kg −1 which is 2.5 times higher than previously reported for piezoelectric textiles. An energy conversion efficiency of 22.5% is achieved for the coiled hybrid piezofiber energy generator. A prototype energy generator and sensors based on a hybrid piezofibers wearable device for energy harvesting and monitoring real time precise healthcare are demonstrated. Abstract : Herein, a new method to create wearable energy generators and sensors using nanostructured hybrid polyvinylidene fluoride/reduced graphene oxide/barium‐titanium oxide piezoelectric fibers and exploiting the enormous variety of textile architectures are presented. Also, a highly stretchable prototype energy generator and sensor based on coil device for energy harvesting and monitoring real‐time precise healthcare is demonstrated.